Development of POE (Predict-Observe-Explain) Oriented Learning Device to Improve Students' Problem-Solving Ability on Environmental Change Material - Windari, Windari; Latjompoh, Masra; Hamidun, Marini Susanti (Universitas Labuhanbatu, 2022)
This study aims to describe the validity, practicality, and effectiveness of POE (Predict-Observe-Explain) oriented learning devices in the form of Lesson Plans (RPP), Student Worksheets (LKPD), Pre-Test & Post-Test Questions. This research uses (R&D), which consists of material analysis, literature study, design of learning devices, validation of learning devices, revision of learning devices, limited scale trials, and producing learning devices that meet the criteria of validity, practicality, and effectiveness. This study involved 15 students at SMAN 1 Gorontalo. The results show that the POE-oriented learning devices (Lesson Plan, Student Worksheet, Questions) obtained the percentage of validation results from 2 expert validators, namely 91.6% Lesson Plan, 93.3% Student Worksheet, and 91.6% Questions & from the practitioner validators obtained a percentage of 97.2% Lesson Plan, 96.6% Student Worksheet and 100% Questions with very valid criteria. The practicality of learning devices from the results of the implementation of learning is 98.16% in the very good category, the student activity is 89.2%, and the student response questionnaire reaches 87.29% in the very good category. The effectiveness of POE learning devices from the results of pre-test & post-test data analysis conducted during learning using the N-Gain test with an average score of 0,85 is in high criteria. Based on the result, it can be concluded that the development of POE-oriented learning devices on environmental change material is appropriate for classroom learning